Unveiling the Advantages and Disadvantages of Chain Stories with Visual Media in Speaking Activities based on Students’ Experiences - Andriani, Agis; Marlina, Neni; Maulida, Eki Rizkia (English Teaching and Linguistics Journal (ETLiJ), 2024)
In Indonesia, where English is learned as a foreign language, speaking is often considered one of the most challenging skills for students to develop. Many students struggle to effectively convey their ideas during speaking activities, frequently feeling uncertain about what to say, which creates a desire for a more engaging and enjoyable learning process. To address this challenge, teachers need to be adept at creating fun and interactive learning experiences, such as utilizing the chain stories technique. The combination of learning techniques with media plays a crucial role in enhancing the speaking-focused English learning experience. This research aims to explore the advantages and disadvantages of using chain stories with visual media in speaking activities, based on students' experiences. A descriptive case study method is employed, with four students from an English course in Tasikmalaya participating in semi-structured interviews. Data is analyzed using thematic analysis. The findings reveal three key advantages of the chain stories approach: increased student motivation, enhanced self-confidence, and its suitability as a recommended learning technique for English classes. However, two disadvantages also emerged: technical problems and knowledge-related challenges during implementation. These insights can assist teachers in weighing the benefits and limitations of using chain stories with visual media as a tool to improve students' speaking skills and enhance the overall English teaching and learning process, particularly in speaking-focused activities.